Konsep Investasi dalam Perspektif Manajemen Keuangan Syariah: Tinjauan Teori dan Prinsip Syariah - Nisa, Nisa; Fitri, Nur; Safitri, Ririn; Rianti, Repa; Putri, Renika Septia (CV. Rayyan Dwi Bharata, 2025)
Wealth is a blessing from Allah to support human life. In Islam, the use of wealth is permitted as long as it is managed productively. One way to enhance the productivity of wealth is through investment, which involves allocating assets or money to gain future profits. Islam strongly encourages investment, as stated in the Qur'an and exemplified by the Prophet Muhammad (peace be upon him). Investment offers significant benefits, such as financial protection and wealth distribution to increase its value and utility. However, not all types of investments are permissible. Islam establishes principles, management, criteria, types, patterns, and risks as guidelines to differentiate between halal and non-halal investments. By adhering to these rules, Muslims can avoid prohibited practices and transform investment into an act of worship, provided it aligns with Sharia principles.